Guided immobilisation of single gold nanoparticles by chemical electron beam lithography - Schaal, Patrick A.; Simon, Ulrich (Beilstein Journal of Nanotechnology, 2013)
The fabrication of periodic arrays of single metal nanoparticles is of great current interest. In this paper we present a straight-forward three-step procedure based on chemical electron beam lithography, which is capable of producing such arrays with gold nanoparticles (AuNPs). Preformed 6 nm AuNPs are immobilised on thiol patterns with a pitch of 100 nm by guided self-assembly. Afterwards, these arrays are characterised by using atomic force microscopy.
Keywords: 2D pattern; indium tin oxide (ITO); positioning; SAM; self-assembly